Effect of different statins on the antifungal activity of polyene antimycotics - Nyilasi, Ildikó (Acta Biologica Szegediensis, 2010)
The antifungal activities of amphotericin B/statin and nystatin/statin combinations against some opportunistic pathogenic fungi (Candida albicans, Candida glabrata, Paecilomyces variotii, Aspergillus fumigatus, Aspergillus flavus and Rhizopus oryzae) were investigated. The in vitro interactions between polyene antifungal drugs and different statins were evaluated using a standard chequerboard broth microdilution method. Most of the detected interactions were additive, though in some cases synergism was also observed. In most cases, the extents of inhibition were higher when these compounds were applied together, and as a result the concentrations of amphotericin B and a given statin, needed to prevent fungal growth, generally could be decreased by some dilution steps.